Inhibition of mesothelioma cancer stem‐like cells with adenovirus‐mediated NK4 gene therapy. Issue 2 (27th December 2014) - Deng, Xu‐Bin; Xiao, Li; Wu, Yue; Jin, Fang; Mossman, Brooke; Testa, Joseph R.; Xiao, Guang‐Hui
<x xml:space="preserve">Abstract</x> Malignant mesothelioma (MM) is a highly invasive and chemoresistant malignancy induced by asbestos fibers. NK4, a hepatocyte growth factor antagonist and angiogenesis inhibitor, consists of the N‐terminal hairpin domain and four kringle domains of the α‐chain of hepatocyte growth factor. The therapeutic potential of NK4 has been demonstrated in a variety of tumor types. However, the mechanisms by which NK4 inhibits tumor growth have not been well delineated. In this study, it is shown that the NK4 adenovirus (Ad‐NK4) potently inhibits cell viability, invasiveness and tumorigenicity of human MM cells. Significantly, this study demonstrates for the first time that Ad‐NK4 inhibits cancer stem‐like cell (CSC) properties as assessed by spheroid formation assay, side population analysis and flow cytometric sorting of CD24 cells. In addition to inhibiting phosphorylation of Met and AKT, Ad‐NK4 markedly suppressed the active form of β‐catenin, a key mediator of both Wnt and AKT pathways. It is further demonstrated that expression of NK4 suppresses β‐catenin nuclear localization and transcriptional activity. Intriguingly, the expression levels of Oct4 and Myc, two critical stem cell factors and downstream targets of β‐catenin, were also diminished by Ad‐NK4. Furthermore, the strong antitumor effect of NK4 was found to be linked to its ability to inhibit CSCs as revealed by immunohistochemical examination of tumor specimens from a mouse xenograft model of human MM. These findings suggest that NK4 acts as a CSC inhibitor by impeding Met/AKT/β‐catenin signaling and holds promise for achieving durable therapeutic responses in MM by constraining the CSC component of these aggressive tumors.